2019
DOI: 10.15171/hpr.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Performance Indicators and Readmission of Patients With Open Heart Surgery: A Case Study in Iran

Abstract: Background: Open heart surgery is a prevalent therapeutic intervention for cardiovascular diseases. Significant adverse effects occur after heart surgery, one of which is patient readmission to the hospital. Objective: The present study aimed to determine the relationship between performance indicators and the readmission of patients with open heart surgery in a teaching hospital in Iran. Methods: This study was performed using a cross-sectional and descriptive method with a retrospective approach. Data was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…This study was similar to the study conducted by Parvin, where 55.4% were female. 1 However, contradicting to this study was the study conducted in Egypt where the majority of respondents were male (67.7%). The reason for this contradiction may be due to their sampling technique where convenience sampling technique was used compared to the simple random sampling technique in the present study.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…This study was similar to the study conducted by Parvin, where 55.4% were female. 1 However, contradicting to this study was the study conducted in Egypt where the majority of respondents were male (67.7%). The reason for this contradiction may be due to their sampling technique where convenience sampling technique was used compared to the simple random sampling technique in the present study.…”
Section: Discussionmentioning
confidence: 64%
“…9 A study conducted in Iran in 2019 found that 30 days of readmission after open-heart surgery was 11.7%, which is nearly comparable to the present study. 1 Similarly, a study in the UK between 2004 and 2010 reported that the 30-day readmission after discharge following cardiac surgery was 7%, which supports these findings. 6 Moreover, a study conducted by Shajedur and reported that the 30-day readmission after discharge following CABG surgery was 12.9%, which is consistent with the present study.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Studies indicated that there are various indices to assess the hospital performance which four of them are the most significant and applicable ones: bed occupancy, bed turnover rate (BTR), average length of stay (LOS), and bed turnover interval (BTI). [ 8 ]…”
Section: Introductionmentioning
confidence: 99%